Controlled gas–liquid interfacial plasmas for synthesis of nano-bio-carbon conjugate materials. (19th December 2017) - Kaneko, Toshiro; Hatakeyama, Rikizo
Abstract: Plasmas generated in contact with a liquid have been recognized to be a novel reactive field in nano-bio-carbon conjugate creation because several new chemical reactions have been yielded at the gas–liquid interface, which were induced by the physical dynamics of non-equilibrium plasmas. One is the ion irradiation to a liquid, which caused the spatially selective dissociation of the liquid and the generation of additive reducing and oxidizing agents, resulting in the spatially controlled synthesis of nanostructures. The other is the electron irradiation to a liquid, which directly enhanced the reduction action at the plasma–liquid interface, resulting in temporally controlled nanomaterial synthesis. Using this novel reaction field, gold nanoparticles with controlled interparticle distance were synthesized using carbon nanotubes as a template. Furthermore, nanoparticle–biomolecule conjugates and nanocarbon–biomolecule conjugates were successfully synthesized by an aqueous-solution contact plasma and an electrolyte plasma, respectively, which were rapid and low-damage processes suitable for nano-bio-carbon conjugate materials.